Isolation of Tritrichomonas foetus from cats sampled at a cat clinic, cat shows and a humane society in southern Ontario. Issue 8 (August 2013) - Hosein, Ansarah; Kruth, Stephen A; Pearl, David L; Richardson, Danielle; Maggs, Jocelyn C; Peach, Hillary A; Peregrine, Andrew S
Tritrichomonas foetus is a protozoan parasite that has been associated with chronic diarrhea in cats. This study aimed to determine (i) the prevalence of T foetus shedding in cats from three different populations in southern Ontario, and (ii) associations between the presence of T foetus and potential cat management, health and demographic risk factors. A cross-sectional study was conducted involving 140 cats from a cat clinic in Guelph, 46 cats from a humane society in Guelph and 55 cats from two cat shows. Risk factor information was assessed through a questionnaire. The InPouch TF (feline) culture method was used to determine the presence of T foetus in all samples. Polymerase chain reaction was conducted on all samples positive by the InPouch TF, as well as 132 negative samples. The assays were interpreted in series and the prevalence of T foetus shedding and 95% confidence intervals (CI) were estimated at 0.7% (95% CI: 0.0–3.9%; n = 140) from the cat clinic, 0% (95% CI: 0.0–7.7%; n = 46) from the humane society and 23.6% (95% CI: 13.2–37.0%; n = 55) from the cat shows. 'Attendance at cat shows' was the only variable significant in both the univariable and multivariable analyses ( P <0.05). No significant association was found between the presence of T foetus and diarrhea at the time of sampling or having a history of diarrhea in the past 6 months. The prevalence of T foetus was highly variable among populations of cats in southern Ontario, with shedding being most common in show cats.